Rethinking DNA testing in the filiation process. An expert evidence not exempt from error - Alfaro Valverde, Luis (2021)
In court, genetic evidence owns the privilege of irrefutability. Judges often use this means of proof uncritically, in other words, without any rational instrument. Rethinking DNA testing suggests a challenge that emphasizes the need for dialogue between law, epistemology and science. In particular, in the filiation process, despite the lack of an epistemic analysis of this scientific test, it has become the “ideal” evidentiary instrument to prove parent-child filiation. Although the particularities of this process, based on DNA, seek to protect the right to identity of minors, which is projected in its speedy nature; however, the risk of error that may exist is not always taken into consideration.In view of this situation, this paper seeks to identify the different cases of risk of error to which one is exposed in the process of filiation, when working with genetic evidence, among others, as the collection of the sample, chain of custody, elaboration of the evidence by the expert, performance and evaluation of the expert’s report. Likewise, some practical criteria are determined, the use of which can guarantee the rational treatment of this expert evidence.